Design of polyazamacrocyclic Gd3+ theranostic agents combining magnetic resonance imaging and two-photon photodynamic therapy. Issue 9 (10th February 2021) - Abad Galán, Laura; Hamon, Nadège; Nguyen, Christophe; Molnár, Enikő; Kiss, János; Mendy, Jonathan; Hadj-Kaddour, Kamel; Onofre, Mélanie; Trencsényi, György; Monnereau, Cyrille; Beyler, Maryline; Tircsó, Gyula; et al.
Abstract : New "all-in-one" theranostic systems, combining a magnetic resonance imaging contrast agent with a biphotonic photodynamic therapy photosensitiser generating cytotoxic singlet oxygen, were successfully developed and characterized. Abstract : New "all-in-one" theranostic systems, combining a magnetic resonance imaging (MRI) contrast agent with a biphotonic photodynamic therapy (2P-PDT) photosensitiser generating cytotoxic singlet oxygen, were envisaged and synthesised. They are based on azamacrocycles, regiospecifically functionalised by two-photon PDT π-conjugated dibromobenzene–picolinate photosensitisers and acetate, able to complex gadolinium(iii ) and allow an MRI signal. Our approach was to use two different macrocyclic platforms, tacn and pyclen, for modulating simultaneously the structures, properties and solubility of the complexes. Photophysical properties of the ligands and their gadolinium(iii ) complexes were fully investigated. The Gd 3+ –pyclen derivative showed the best water solubility and the greatest value of singlet oxygen generation of the series with Φ Δ = 0.53 enabling in vitro studies. The biological PDT activity under mono and biphotonic excitation was evaluated in human breast cancer cells (MCF-7). While a very low dark toxicity was observed, an almost total cell death was induced after only 3 successive irradiations of 1.57 s. Finally, its relaxivity was measured in a DMSO/H2 O solvent mixture with r 1p = 11.21 and r 2p = 24.60 mM −1 s −1 at 3.0 T and T 1 - and T 2 -weighted phantom MR images were obtained highlighting a first generation of "all-in-one" PDT/MRI theranostic agents.